Applying Blended Learning To Teach Vocabulary To Fourth Semester Students For English Department Students At Christian University Of Indonesia Toraja - Roni La’biran (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2021)
The goal of the research is to know the effect of blended learning applied in teaching vocabularies for the fourth semester students. The research used qualitative method. The subject of the research is lecturer and fourth semester students at Toraja Christian University of Indonesia. The data collected by using edmodo as a media that used in pretest and posttest and zoom application used presented. In the research has effective indicator in teaching process. After applying blended learning, the result showed raised score, it can be classified excellent is 4 percent, very good is 28 percent , and fair is 44 percent, and poor is 1 percent